Comparison of the Effectiveness of Cognitive-Behavioral Therapy and Short-Term Solution-Focused Therapy on Distress Tolerance in Pregnant Women - Irvani, Farnoosh; Bolghan-Abadi, Mustafa; Mansouri, Ahmad (Health Nexus, 2025)
The present study aimed to compare the effectiveness of cognitive-behavioral therapy (CBT) and short-term solution-focused therapy (SFBT) on distress tolerance in pregnant women in 2024. This applied research employed an experimental design with pretest–posttest and follow-up assessments, including a control group. The study population comprised all pregnant women who visited the Comprehensive Health Service Center and obstetrics specialists in Semnan and who became pregnant either naturally or through assisted reproductive methods in 2021 and 2022. Using a convenience sampling method, 66 pregnant women were selected. Data were collected using the standardized Distress Tolerance Scale (DTS) by Simons and Gaher (2005) and analyzed with SPSS version 27. The CBT intervention group participated in eight weekly sessions of 90 minutes each, while the SFBT intervention group attended six weekly sessions of 90 minutes each. The control group was placed on a waiting list. The results showed that both CBT and short-term SFBT significantly improved distress tolerance in pregnant women, indicating the effectiveness of both therapeutic approaches. Additionally, no statistically significant difference was found between the two intervention groups regarding their impact on increasing distress tolerance. Based on the findings, both CBT and short-term SFBT were effective in enhancing distress tolerance and demonstrated stable effectiveness over time. Therefore, it is recommended that behavioral therapy practitioners incorporate the results of this study into their therapeutic programs